An ultra-sensitive biosensor based on surface plasmon resonance and weak value amplification - Zhang, Lizhong; He, Mingyi; Xu, Yang; Guo, Cuixia; Zhou, Chongqi; Guan, Tian (Frontiers in Chemistry, 2024)
An ultra-sensitive phase plasmonic sensor combined with weak value amplification is proposed for the detection of IgG, as a model analyte. Phase detection is accomplished by self-interference between the p-polarization and the s-polarization of the light. With the principles of weak value amplification, a phase compensator is used to modulate the coupling strength and enhance the refractive index sensitivity of the system. On a simple Au-coated prism-coupled surface plasmon resonance (SPR) structure, the scheme, called WMSPR, achieves a refractive index sensitivity of 4.737 × 10 4 nm/RIU, which is about three times higher than that of the conventional phase-based approach. The proposed WMSPR biosensor gives great characteristics with a high resolution of 6.333 × 10 -8 RIU and a low limit of detection (LOD) of 5.3 ng/mL. The results yield a great scope to promote the optimization of other SPR biosensors for high sensitivity.